2011
DOI: 10.1111/j.1751-0813.2011.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Omentalisation of a caudal mediastinal abscess in a dog

Abstract: A caudal mediastinal abscess was diagnosed in a 2-year-old German Short-haired Pointer with acute onset of lethargy, pyrexia and tachypnoea. The abscess was managed surgically by median sternotomy, abscess content evacuation and omentalisation of the abscess cavity via the diaphragm. Although surgical management of mediastinal abscesses has been reported previously, this is the first report to describe successful management of the condition in a dog by omentalisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…all other hospital presentations) demonstrated Border Collies, spaniels, Golden Retrievers, Kelpies, Labrador Retrievers, Staffordshire Bull Terriers and Shih Tzus were at a significantly increased risk of developing GSFBD. Recent studies reported GSFBD in the Cocker Spaniel, English Pointer and German Short‐haired Pointer in Australia; however, those reports were isolated case studies and did not attempt to document the prevalence of GSFBD in these breeds compared with the overall dog population. In this current study univariable logistic regression showed that breed was a significant factor in the development of GSFBD, but more work is required to identify the precise factors involved.…”
Section: Discussionmentioning
confidence: 99%
“…all other hospital presentations) demonstrated Border Collies, spaniels, Golden Retrievers, Kelpies, Labrador Retrievers, Staffordshire Bull Terriers and Shih Tzus were at a significantly increased risk of developing GSFBD. Recent studies reported GSFBD in the Cocker Spaniel, English Pointer and German Short‐haired Pointer in Australia; however, those reports were isolated case studies and did not attempt to document the prevalence of GSFBD in these breeds compared with the overall dog population. In this current study univariable logistic regression showed that breed was a significant factor in the development of GSFBD, but more work is required to identify the precise factors involved.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, its ability to contain, resolve and wall off sites of abscessation has proved useful in the management of abscesses in the mediastinum (Franklin and others 2011), pancreas (Johnson and Mann 2006) and prostate gland (White 2000). A similar combination of surgical exploration, debridement, omentalisation and postoperative antibiotic therapy was used in this case series for the management of abscessation of the sublumbar muscles and resulted in long-term resolution of the condition in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Diseases of the mediastinal pleura are uncommon but include neoplasia, mediastinitis and chronic abscessation (Radlinsky 2012). Mediastinitis and mediastinal abscessation have been most commonly reported as a complication of pyothorax (Rooney and Monnet 2002, Schultz and Zwingenberger 2008, Franklin and others 2011, Brissot and others 2012), the underlying cause for which is often suspected to be inhaled or ingested foreign material (Koutinas and others 2003, Brissot and others 2012). Even if there is no single breed predilection, hunting and working-type dogs are reported to be over-represented (Demetriou and others 2002, Rooney and Monnet 2002, Scott and Macintire 2003b, Johnson and Martin 2007).…”
Section: Introductionmentioning
confidence: 99%